PENGUATAN SIKAP PEDULI LINGKUNGAN SEJAK DINI MELALUI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Ida Mawaddah; Dewi Ratna Muchlisa M; Sudarsono Sudarsono (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
This study aims to identify effective learning methods in improving environmental awareness in fifth-grade elementary school students through the Problem-Based Learning (PBL) model in Natural and Social Sciences (IPAS) subjects. IPAS, as a subject that covers social, economic, and environmental aspects, has great potential to shape students' character and environmental insight. Given the importance of environmental awareness from an early age, elementary education is an important stage in building environmental values and attitudes. This study uses a qualitative approach with a descriptive method. Data collection was carried out through observation, interviews, and in-depth literature studies. The findings of the study indicate that incorporating environmental issues into IPAS teaching can improve students' cognitive abilities and improve their understanding of environmental conservation values. Some strategies that have proven effective include the use of innovative learning media, group discussion methods, and environmental-based projects. Students' critical thinking skills and understanding of sustainable concepts are strengthened in addition to their factual knowledge. This study suggests the use of learning models that are appropriate to students' needs and finds that it is important for teachers to be able to develop more creative curriculum materials and address environmental issues.